Morphometric changes of the left ventricle and characteristics of peripheral hemodynamics in patients with drug resistant hypertension - R. R. Kushkhova; A. G. Avtandilov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study morphometric changes of the left ventricle (LV) and characteristics of peripheral hemodynamics in patients with drug resistant hypertension (HT).Material and methods. In total, 120 patients with unmanageable HT of 2-3 degrees, that considered by physicians as drug resistant HT, were included into the study. Patients with HT resistant to full-dose triple antihypertensive therapy (n=43) were included into Group 1. Patients with HT controlled by combination therapy (n=83) were included into Group 2. All the patients underwent echocardiography, volumetric compression oscillometry (to study hemodynamic parameters). Stiffness index (SI, m/s) and reflection index (RI,%) of the pulse wave were also analyzed.Results. The increase in linear and volumetric LV sizes, severe LV hypertrophy were found in Group 1. LV mass index (LVMI) in patients in Group 1 was 134.0±6,5g/m² vs 98.4±3.3 g/m² in Group 2 (p<0.001). LVMI in men in Group 1 was 150.02±10.7 g/m² vs 99.2±4.5 g/m² in Group 2 (p<0.001). LVMI in women in Group 1 was 126±7.8 g/m vs 102.5±3.4 g/m² in Group 2 (p<0.05). The relative left ventricular wall thickness in Group 1 was 0.60, vs 0.50 in Group 2 (p<0.05). In patients of group 1 compared with group 2 there were also found a reduction in arterial compliance (0.84±0.06 vs 1.0±005, respectively; p<0.05), increased pulse wave velocity (820.14±16 vs 741.11±19 cm/sec, respectively; p<0.05), and increase in specific peripheral vascular resistance.Conclusion. Most of patients with drug resistant HT have concentric LV hypertrophy and concentric LV remodeling. The microvasculature remodeling takes place much earlier and is accompanied by possible rarefaction. Increased vascular stiffness is more pronounced in patients with drug resistant HT. It was confirmed by decrease in arterial compliance, and increase in outer diameter of the artery, that led to increase in pulse wave velocity